Optimization of Inventory Level to Uncertain Demand Using Bayesian Approach - Isnaini, M.; Tirta, I Made; Pradjaningsih, Agustina (Jurusan Matematika FMIPA Universitas Jember, 2016)
The decision to determine grade of optimum supply on uncertainty demand or mainly unknowing could accomplish with Buyer-approach method.The demand with mainly unknowing can assumed as Poisson distribute.Completion with Buyer-approach method could be starting with count of posterior Gamma have distributed from prior Gamma with α and ß parameter. At the end the result of counting above can compared with proportion between supply and demand until we get a stable-grade of supply.